Smart License Plate in Combination with Fluorescent Concentrator for Vehicular Visible Light Communication System - Seoyeon Oh; Yejin Lee; Minseok Yu; Seonghyeon Cho; Sana Javed; Hyunchae Chun (Sensors, 2022)
Vehicle-to-vehicle communication based on visible light communication has gained much attention. This work proposes a smart license plate receiver incorporated with a fluorescent concentrator, enabling a fast vehicle-to-vehicle communication with a large field of view and high optical gain. Communication performance is experimentally analyzed using off-the-shelf light-emitting diode-based headlamps for low-latency direct line of sight channel. Additionally, a blue laser diode-based beam-steering and tracking system, through image processing of taillights with a steerable mirror, is investigated. Data rates of 54 Mbps from the headlamps and 532 Mbps from the beam-steering channel with ±25° are demonstrated. In addition, real-time video streaming through the beam-steering channel is presented.